ANALISIS KEMAMPUAN PEMAHAMAN MATEMATIS SISWA MA - Acep Pebianto; Luvy Sylviana Zanthy (Journal on Education, 2019)
This research aims to analyze the mistakes of students in solving mathematical understanding and ability to question the extent to which students do such errors as well as to know the level of understanding of its mathematical ability. The methods used in this research is descriptive qualitative approach.The results obtained from this study showed that the percentage of indicators to apply the concept in mathematical algorithms in the ability of understanding the students, get the lowest percentages with percentage of 34.72% on question No. 4. Then the errors committed students in resolving the question of the ability of mathematical understanding is located on some of the aspects that is mistaken in applying the concepts in resolving the problem, as well as mistaken in operation count. The level of understanding of the mathematical ability of students still belongs to low visible from the large number of errors committed students in resolving the question of mathematical understanding ability test.